2021
DOI: 10.1096/fj.202100299r
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of LSR from tricellular corners causes macropinocytosis at cell–cell interface as a trigger for breaking out of contact inhibition

Abstract: Withdrawal from contact inhibition is necessary for epithelial cancer precursor cells to initiate cell growth and motility. Nevertheless, little is understood about the mechanism for the sudden initiation of cell growth under static conditions. We focused on cellular junctions as one region where breaking out of contact inhibition occurs. In well‐differentiated endometrial cancer cells, Sawano, the ligand administration for tricellular tight junction protein LSR, which transiently decreased the robust junction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 81 publications
(179 reference statements)
0
8
0
Order By: Relevance
“…These processes involve the activation of the RhoG-Rac pathway and reorganization of actin filaments [ 35 ]. Recently, it was reported that macropinocytosis is necessary for breaking out contact inhibition and initiating stratified cell growth in well-differentiated human endometrial cancer cells ( Figure 1 ) [ 4 ]. While macropinocytosis, which is Rac-dependent, occurs through the temporary split of adjacent cell junctions; there is no protrusion of the cell membrane prior to macropinocytosis.…”
Section: A Universal Role Of Macropinocytosismentioning
confidence: 99%
See 4 more Smart Citations
“…These processes involve the activation of the RhoG-Rac pathway and reorganization of actin filaments [ 35 ]. Recently, it was reported that macropinocytosis is necessary for breaking out contact inhibition and initiating stratified cell growth in well-differentiated human endometrial cancer cells ( Figure 1 ) [ 4 ]. While macropinocytosis, which is Rac-dependent, occurs through the temporary split of adjacent cell junctions; there is no protrusion of the cell membrane prior to macropinocytosis.…”
Section: A Universal Role Of Macropinocytosismentioning
confidence: 99%
“…Sawano cell was established by endometrial adenocarcinoma of uterus [ 63 ]. Sawano has a KRAS G13D heterozygous mutation and wild-type BRaf [ 4 ]. According to this study, Sawano cells have high planar motility at low cell densities, whereas at high cell densities, their growth and motility are temporarily arrested due to contact inhibition.…”
Section: Disruption Of Epithelial Homeostasis Triggers Cancer Malignancymentioning
confidence: 99%
See 3 more Smart Citations